Help-seeking behaviour following school-based screening for current suicidality among European adolescents - Cotter, Pádraig; Kaess, Michael; Corcoran, Paul; Parzer, Peter; Brunner, Romuald; Keeley, Helen; Carli, Vladimir; Wasserman, Camilla; Hoven, Christina; Sarchiapone, Marco; Apter, Alan; Balázs, Judit; et al. (Social psychiatry and psychiatric epidemiology, 2015)
To screen and clinically interview European adolescents reporting current suicidality (suicidal ideation and suicide attempt) and investigate attendance at the clinical interview.
Gesehen am 18.03.2020